AN ANALYSIS OF STUDENT'S DIFFICULTIES IN ENGLISH READING SKIMMING TEXT AT GRADE X MA MUHAMMADIYAH BENGKULU - Hani Indriyani Hani; Ali Akbar Jono; Ferri Susanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Reading is an essential skill in learning English as a Foreign Language (EFL) because it plays a significant role in developing students’ academic abilities and knowledge. One of the rapid reading techniques introduced at the Madrasah Aliyah level is skimming, which is used to obtain the general idea and main points of a text without reading it in detail. However, based on preliminary observations at MA Muhammadiyah Bengkulu, many students still experience difficulties in applying skimming techniques effectively. Therefore, this study aims to analyze students’ difficulties in reading English texts using skimming techniques and to identify the factors causing these difficulties. This research employed a descriptive qualitative approach. The participants were 15 tenth-grade students of MA Muhammadiyah Bengkulu selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation. The data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that students faced several difficulties in applying skimming techniques, such as identifying the main idea, understanding vocabulary, locating word references, making inferences, and finding detailed information in the text. The main factors contributing to these difficulties were limited vocabulary mastery, students’ lack of understanding of skimming strategies, and insufficient practice in reading English texts. Based on these findings, it can be concluded that students’ skimming ability still needs improvement through more structured reading instruction, appropriate strategy application, and continuous practice in order to help students comprehend English texts more effectively and efficiently.